Comparing snowpack surface roughness metrics with a geometric-based roughness length - Fassnacht, S. R., author; Oprea, I., author; Borleske, G., author; Kamin, D., author; Colorado State University, publisher (Colorado State University. Libraries, 2014)
The snow surface is the interface between the atmosphere and the earth. It is very dynamic, and varies spatially and temporally. Its roughness influences turbulence and is used to estimate the sensible and latent heat fluxes to and/or from the snow surface to the atmosphere. We use airborne lidar-derived snow surface measurements from the NASA Cold Land Process Experiment Fraser Alpine intensive study area (ISA) collected in late March 2003. A meteorological tower was centered in the middle of the 1 km2 ISA and meteorological data were used to determine the dominant wind direction. The raw surface elevation data were rotated to yield a 100 by 100m area about the tower, that was parallel to the wind. The data were interpolated to a 1-m resolution using four methods to purposefully derive four different snowpack surfaces. Roughness metrics, including the random roughness, autocorrelation, and fractal dimension were computed, and compared to the geometric-based roughness which was derived using the Lettau formulation.
Hydrology days 2014
AGU hydrology days 2014
2014 annual AGU hydrology days was held at Colorado State University on March 24 - March 26, 2014.